2011
DOI: 10.1088/0004-637x/745/1/76
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Pulse of GRB 090618: A Simultaneous Spectral and Timing Analysis of the Prompt Emission

Abstract: We develop a new method for simultaneous timing and spectral studies of Gamma Ray Burst (GRB) prompt emission and apply it to make a pulse-wise description of the prompt emission of GRB 090618, the brightest GRB detected in the Fermi era. We exploit the large area (and sensitivity) of Swift /BAT and the wide band width of Fermi/GBM to derive the parameters for a complete spectral and timing description of the individual pulses of this GRB, based on the various empirical relations suggested in the literature. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 51 publications
(59 reference statements)
0
32
0
Order By: Relevance
“…Moreover, the correct shape of the thermal component is debatable. For example, the timeresolved spectra of GRB 090902B are consistent with a variety of models -a single blackbody with a powerlaw (BBPL; Zhang et al 2011), a multicolour blackbody along with a power-law (mBBPL; Ryde et al 2010), and two blackbodies with a power-law (2BBPL; Basak & Rao 2013a;Rao et al 2014). Such a diversity in the spectral models is perhaps due to the limited energy resolution and/or bandwidth of the instruments used for GRB spectral analysis.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover, the correct shape of the thermal component is debatable. For example, the timeresolved spectra of GRB 090902B are consistent with a variety of models -a single blackbody with a powerlaw (BBPL; Zhang et al 2011), a multicolour blackbody along with a power-law (mBBPL; Ryde et al 2010), and two blackbodies with a power-law (2BBPL; Basak & Rao 2013a;Rao et al 2014). Such a diversity in the spectral models is perhaps due to the limited energy resolution and/or bandwidth of the instruments used for GRB spectral analysis.…”
Section: Introductionmentioning
confidence: 66%
“…The value of α, however, is not always compatible with this non-thermal model, and sometimes is found to be even greater than the maximum value allowed in a slow cooling regime, -2/3 (Crider et al 1997(Crider et al , 1999Preece et al 1998). In addition, evidence for a thermal component has been seen in a few bright GRBs (e.g., Ghirlanda et al 2003;Ryde 2004Ryde , 2005Shirasaki et al 2008;Ryde & Pe'er 2009;Guiriec et al 2011Guiriec et al , 2013Axelsson et al 2012;Basak & Rao 2013b;Rao et al 2014). The spectrum contains either only a thermal component, or a combination of a thermal and a non-thermal component.…”
Section: Introductionmentioning
confidence: 99%
“…Pulse-wise analysis not only restores the correlation, it improves that (0.89). They used the pulse description of Basak & Rao (2012a) and found that replacement of E peak with a new quantity of their model, namely the peak energy at zero fluence (E peak,0 ) improves the correlation even further (0.96).…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…4 For this we use the spectral model as Band function 9 , lightcurve as Norris model 10 and spectral evolution as Liang-Kargatis model…”
Section: Pulse-wise Grb Correlationmentioning
confidence: 99%
“…In recent works, 4,5 we have given particular attention to the individual GRB pulses and obtained the timing and spectral informations. We have then used the GRB pulses to study GRB correlations 6,7 similar to the Amati correlation 8 .…”
Section: Introductionmentioning
confidence: 99%